Cassava farmers' insights and seed dealers enterprises in Nigeria - Balogun, D.O. (University of Ibadan, 2019)
Seed enterprise is an initiative and risk set up in the production of cassava stems from existing local seed varieties or improved seed varieties for economically sustainable profit. Although, most cassava seeds produced are through informal seed system among smallholder farmers but there is need for replacement strategy for cassava seeds mostly planted over years. Based on this, there is need for intense exploration in the linkage between cassava seed management and diffusion scheme among rural farmers. The study was conducted to investigate the insight of cassava farmers’ and seed dealers’ enterprise in selected agro ecological area in Osun, Benue, Imo and Akwa-Ibom states. One hundred and ninety-six farmers’ marketers were sampled using multi-stage sampling procedure. Variables measured included respondents’ socioeconomic characteristics, the use of accessed cassava seed for production based on potential benefit, sources of information, willingness to adoption of cassava seeds, perception to cassava seed enterprise and constraints in the use of accessed cassava seeds. Data were analyzed using frequencies counts, percentages and inferential statistical tools such as Chi-square, PPMC and ANOVA at p=0.05 The result shows that majority (57.6%) of the respondents were between the age of 20 and 45 years, (85.2%) are married and had between primary and secondary education , household size (75.5%) was between one and eight persons, (58.1%) had 10 to 25years of farming experience with (85.3%) less than 0.5hectares of farm size. Majority (88.3%) of the farmers pointed that accessed cassava seeds produce varieties that maintain bright color appearance from fresh root to mash and finally to white color processed garri. Farmers were very willing (38.5%) to adopt cassava seed to generate income because there is wealth potential in seed enterprise. Majority (66.3%) of the respondents strongly agreed that growth rate of stem influence farmers’ perception to seed enterprise. Constraint to access cassava seeds were very serious with (89.3%) lack of access to agricultural loan, (29.1%) on lack of money to expand farmland. There was significant relationship between the use of farmers’ accessed cassava seed based on potential benefits and perceptions on seed enterprise (r = 0.436, p=0.000) and their willingness to adopt cassava seeds (r=0.287, P=0.000). If accessed cassava seeds have potential benefit for post-harvest use and farmers have favorable perception (53.1%) towards cassava seeds enterprise except in Benue state where there was disparity within farmers’ willingness. This means if there is easy access to farmers’ preferred seed qualities and appropriate seed channels could be designed within the local system and efforts are made to solve the perceived constraints, the sustainability of cassava seed enterprise would be achieved and old seeds on farmers field would be replaced.